Estudo da influencia do índice de fluidez na cinética de cristalização de blendas de PP-Homopolímero/PP-Copolímero heterofásico e propriedades de compósitos com argila organofílica - Campos, Diego Adalberto Teles (2020)
This work aimed to study the influence of the homopolymer PP (PP-h) melt flow index on the non-isothermal crystallization kinetics, on the rheological, thermal and mechanical properties of the homopolymer PP (PP-h) blends with heterophasic copolymer PP (PP-co). Composites of the polymeric blends of PP-h/PP-co were also produced, with organophilic clays as reinforcing dispersed phase. The blends were obtained using a single screw extruder, varying the content of PP-co in: 25, 50 and 75%, and the composites of these blends were produced using 3 and 5% Cloisite 10A and 20A clays. The study of the thermal properties of the blends was performed using Differential Scanning Calorimetry (DSC) and the Jeziorny and Kissinger methods were used to evaluate the non-isothermal crystallization kinetics. The rheological properties were evaluated in dynamic oscillatory regime and the mechanical properties were investigated under tensile and impact strength of the Izod type. The results indicated that the variation of the PP-h melt flow index and the PP-co content influenced the thermal and rheological behavior of the studied polymer blends. It was observed that the components are miscible with each other, confirmed through the evaluation of the results of the mechanical properties, since, for all compositions, the values obtained xi were intermediate in relation to their pure components. Considering the clays used, it was observed that there was no significant variation in tensile strength depending on the type of clay. For impact resistance, the higher the copolymer content, the greater the impact resistance, in the blends and their composites for both studied fluidity indexes. For the crystallization kinetics, using the Jeziorny method, it was found that the polypropylene heterophasic copolymer does not change the nucleation mechanism. And the crystallization activation energy calculated by the Kissinger method, indicated that it decreased for all blends in the presence of heterophasic polymer for both melt flow index studied, indicating a greater ease of crystallization in the presence of heterophasic polypropylene.